Nutrient‐use strategy and not competition determines native and invasive species response to changes in soil nutrient availability. Issue 5 (5th May 2021) - Knauf, Amanda E.; Litton, Creighton M.; Cole, Rebecca J.; Sparks, Jed P.; Giardina, Christian P.; Gerow, Kenneth G.; Quiñones‐Santiago, Melanie
Abstract : Non‐native invasive plants often outcompete native species under high resource availability. Restoration techniques that lower resources may, therefore, create favorable conditions for resource conservative native species over resource exploitative invasive species. Research on this topic has focused on temperate grass and forb‐dominated ecosystems and has rarely been tested for woody species or tropical vegetation. We evaluated growth, resource‐use efficiency (RUE), ecophysiology, and competition (i.e. a relative interaction index based on biomass) of four woody native and two dominant invasive species from Hawaiian wet and dry tropical ecosystems in a greenhouse experiment. Density of plants was constant and species were grown with either a conspecific or the invasive species from that ecosystem type across a gradient of soil nutrient availability. Instantaneous photosynthetic rates varied minimally across nutrient availability. However, both invasive and one native species increased leaf area as nutrients increased, providing more photosynthetic area and increasing total biomass. Nitrogen RUE decreased with increasing nutrient availability for all but one native species, while phosphorus RUE remained constant for all but one native species. Competitive interactions were weak, variable, and not significantly impacted by soil nutrients. Overall, plants categorized as invasive or resource exploitative had larger changes in response variables with increasing soil nutrients compared to those categorized as native or resource conservative. These results suggest that manipulating soil nutrient availability is a potentially viable restoration tool for at least some woody species in tropical ecosystems. However, predicting restoration success requires understanding species‐specific ecophysiological traits determining response to altered environmental conditions.